I hate Fairyland - Young, Skottie 1978- (Image Comics, 2017)
Follow Gert, a forty year old woman stuck in a six year olds body who has been stuck in the magical world of Fairyland for nearly thirty years. Join her and her giant battle-axe on a delightfully blood soaked journey to see who will survive the girl who HATES FAIRYLAND.
Keywords: Fairyland (Imaginary place) -- Comic books, strips, etc; Girls -- Comic books, strips, etc; Fantasiewelt; Mädchen; Comic